KEBIJAKAN PEMBERIAN KREDIT KEPADA DEBITUR BANKALTIM - Anisa Rahmawati; Zainal Ilmi; Irsan Tricahyadinata (Fakultas Ekonomi Dan Bisnis Universitas Mulawarman, 2017)
The phenomenon in this study is how the influence of internal factors bankaltim including credit risk by proxy Non Performing Loan (NPL), Third Party Funds, Liquidity by proxy Loan to Deposit Ratio (LDR), as well as the level of business efficiency by using the proxy Operating Cost to Revenue operations to the volume of lending to the debtor. Tools statistical test used SPSS version 21 and Ms.Kingsoft 2014. While the data used is secondary data and time series data types in the form of financial ratios related to the vulnerable period of 2008 - 2015. The statistical method used to test the hypothesis that Test Classical assumptions, and multiple linear regression analysis. The conclusion of this study is the variable Non Performing Loan (NPL) and variable Operating Expenses to Operating Income respectively negatively affect the volume of lending, while variable Third Party Fund and variable Loan to Deposit Ratio (LDR) have a positive influence on the volume of lending. The implications of this study are expected bankaltim as a regional bank in East Kalimantan can optimize its lending volume and can maximize Third party funds and maintain financial ratios in accordance with BankÂindonesia.Keywords: Volume of Credit, Non Performing Loan (NPL), Third Party Fund (DPK), Loan to Deposit Ratio (LDR) and Operating Cost to Operating Income BOPO)